(untitled) (Research, Society and Development, 2022)
We sought to perform the carbon equivalent balance in coffee plantations occupied with two cultivars. The study was conducted in 2021, on an agricultural property located within the municipalities of Guaxupé - MG and Tapiratiba - SP, Brazil. We evaluated two plots (A and B), planted in 2018 with a spacing of 3.5 x 0.7 m. The plot "A" occupied with the cultivar Acaia IAC 474-19 and the plot "B" with the cultivar Catuaí IAC-99. The emission estimate was calculated using the GHG Protocol, Ministry of Science, Technology and Innovation and Intergovernmental Panel on Climate Change (IPCC). The carbon present in the biomass was quantified from the slaughter of the plants, determination of moisture (%), carbon content (C) and estimation of carbon dioxide equivalent (CO2 eq). The carbon equivalent balance per hectare (CO2 eq ha-1) was obtained by the difference between the sequestered carbon and the estimated emissions. The results showed that the equivalent carbon sequestration in the coffee biomass in 3.5 years was approximately 3.6 times greater than the emissions. The removal of CO2 eq at 3.5 years was estimated at 15.15 and 24.92 Mg CO2 eq ha-1 for the cultivars Catuai IAC-99 and Acaia IAC 474-19, respectively. Emissions over the evaluated period were 5.05 and 5.77 Mg CO2 eq ha-1 for plots cultivated with Catuaí IAC-99 and Acaia IAC 474-19. Therefore, the production system evaluated at 3.5 years can be considered carbon neutral.